The gallery of miracles and madness : insanity, modernism, and Hitler's war on art - English, Charlie (Random House, 2021)
"The thousands of paintings, drawings, and pieces of sculpture Hans Prinzhorn gathered from German asylums in the early 1920s displayed a raw, expressive power that would change the course of art history. When a new generation of modernists discovered his collection--Max Ernst, André Breton, and Slavdor Dalí among them--they borrowed its ideas to inform their own investigations of the human psyche. But by the 1930s, Prinzhorn's artist-patients and their delicate creations had begun to attract attention of a different kind. Rejected from art schools as a young man, Adolf Hitler saw modernism's interest in madness as a threat: a Jewish-Bolshevik plot aimed at degrading the Aryan soul. Once in power, he ordered modernist paintings and sculpture to be stripped from German galleries and publicly shamed in exhibitions of "degenerate art", alongside "insane" material from the Prinzhorn collection... By 1941, his regime had killed 70,000 psychiatric patients in an extermination campaign that would serve as the prototype from the Final Solution. This is the spellbinding, emotionally resonant story of those artists, of modernism's obsession with the schizophrenic realm, and Hitler's use of that connection to achieve his own genocidal ends"--Dust jacket flap.